Supplementary posterior fusion in patients operated on employing TLIF may decrease the instrumentation failure rate - Bokov, Andrey; Kalinina, Svetlana; Khaltyrov, Mingiyan; Pavlova, Svetlana; Bulkin, Anatoliy (Frontiers in Surgery, 2023)
Background It is supposed that additional posterior fusion may provide additional stability of the pedicle screw; however, the clinical impact of additional posterior fusion in patients treated with TLIF remains uncertain. The objective of this study is to assess the clinical efficacy of circumferential fusion in patients treated with TLIF. Materials and methods This is a single-center retrospective evaluation of consecutive 179 patients with degenerative lumbar stenosis and instability of spinal segments. Patients with axial pain and neurogenic claudication or radiculopathy associated with spinal stenosis were enrolled during the period from 2012 to 2018. Transforaminal lumbar interbody fusion (TLIF) with a single cage was used to treat patients. In 118 cases a supplementary posterior fusion was made. The duration of follow-up accounted for 24 months, logistic regression analysis was used to assess factors that influence the complication rate. Results The rate of pedicle screw loosening was growing with radiodensity getting decreased and was more frequent in patients with two level fusion. An increase in pedicle screw loosening rate correlated with anterior nonunion Tan 2 and 3 grade while both posterior complete and incomplete fusion resulted in a decline in the complication rate. Lumbosacral fusion, bilateral facet joints` resection and laminectomy turned out to be insignificant factors. The overall goodness of fit of the estimated general multivariate model was χ2 = 87.2230; P < 0.0001. To confirm clinical relevance of those findings, a univariate logistic regression was performed to assess the association between clinically significant pedicle screw instability and posterior fusion in patients operated on employing TLIF. The results of logistic regression analysis demonstrate that additional posterior fusion may decrease the rate of instrumentation failure that requires revision surgery in patients treated with TLIF [B0 = 1.314321; B1 = −3.218279; p = 0.0023; OR = 24.98507; 95% CI (3.209265; 194.5162), the overall goodness of fit of the estimated regression was χ2 = 22.29538, p = <0.0001]. Conclusion Circumferential fusion in patients operated on employing TLIF is associated with a decline in the rate of pedicle screw loosening detected by CT imaging and clinically significant instrumentation failure.